Effect of alignment angle on the alignment accuracy of a miniature rotation robot for microscopy imaging. (22nd May 2017) - Wan, Wenfeng; Lu, Haojian; Shen, Shihui; Shen, Yajing
Most recently, a miniature rotation robot has been proposed to allow imaging samples from multidirection for the first time. However, one existing problem for that rotation robot is that the alignment efficiency and accuracy is affected greatly by the alignment angle. This article investigates the effect of alignment angle on the alignment accuracy. Alignment accuracy is measured by sample's position shift during a 360° rotation. Firstly, the miniature robotic system and its alignment principle are introduced briefly. Then, the source of alignment error is analyzed and the error model is built. After that, simulation results are given and indicate that as alignment angle increases, alignment error first decreases, then becomes stable and finally increases. Reasons for the trend of alignment error are explained. Finally, experiment results are demonstrated and have a good agreement with theoretical analysis and simulation results. The results indicate that 90° should be chosen as the alignment angle to ensure both alignment accuracy and alignment speed.